Enrichment of colloidal solutions by nanoparticles in underwater spark discharge - Lopat’ko, K.; Aftandiliants, Y.; Veklich, A.; Boretskij, V.; Taran, N.; Batsmanova, L.; Trach, V.; Tugai, T. (Вопросы атомной науки и техники, 2015)
The underwater spark discharge between manganese granules was studied. Optical emission spectroscopy meth-ods were used for diagnostics of such discharge plasma. The colloidal solution with manganese nanoparticles was produced by this discharge. The biological applications of this colloid were analyzed. The mechanism of metallic nanoparticle action and their transformation at interacting with biological objects were studied in Alternaria alternata culture. Исследовали подводный искровой разряд между гранулами марганца. Для диагностики такой разрядной плазмы использовали методы оптической эмиссионной спектроскопии. Этот разряд использовался для приготовления коллоидного раствора с наночастицами марганца. Проанализированы биологические применения такого коллоида. Механизм воздействия наночастиц металла и их трансформация при взаимодействии с биологическими объектами изучались на культуре Alternaria alternata. Досліджували підводний іскровий розряд між гранулами марганцю. Для діагностики такої розрядної плазми використовували методи оптичної емісійної спектроскопії. Цей розряд використовували для приготування колоїдного розчину з наночастинками марганцю. Проаналізовані біологічні застосування цього колоїду. Механізм дії наночастинок металу та їх трансформація при взаємодії з біологічними об'єктами вивчалися на культурі Alternaria alternata.